2021
DOI: 10.3389/fphys.2021.736211
|View full text |Cite
|
Sign up to set email alerts
|

The Disturbing Effect of Neuromuscular Fatigue on Postural Control Is Accentuated in the Premenstrual Phase in Female Athletes

Abstract: This study explored the fatigue effect on postural control (PC) across menstrual cycle phases (MCPs) in female athletes. Isometric maximal voluntary contraction (IMVC), the center of pressure sway area (CoParea), CoP length in the medio-lateral (CoPLX) and antero-posterior (CoPLY) directions, and Y-balance test (YBT) were assessed before and after a fatiguing exercise during the follicular phase (FP), mid-luteal phase (LP), and premenstrual phase (PMP). Baseline normalized reach distances (NRDs) for the YBT we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…These findings have been confirmed more recently by other authors, who reported increased plantar fascia elasticity, reduced balance, and increased tremor during the ovulatory phase with an increased potential risk of falling (23)(24)(25). In contrast, other authors have shown that the risk of ACL injury increases and neuro-muscular control worsens at the beginning of the follicular phase (7,26) or in the luteal phase in women with Premenstrual Symptoms (8,27,28). In fact, premenstrual syndrome may reduce concentration causing an alteration in the correct execution of a complex 29).…”
Section: Discussionsupporting
confidence: 55%
“…These findings have been confirmed more recently by other authors, who reported increased plantar fascia elasticity, reduced balance, and increased tremor during the ovulatory phase with an increased potential risk of falling (23)(24)(25). In contrast, other authors have shown that the risk of ACL injury increases and neuro-muscular control worsens at the beginning of the follicular phase (7,26) or in the luteal phase in women with Premenstrual Symptoms (8,27,28). In fact, premenstrual syndrome may reduce concentration causing an alteration in the correct execution of a complex 29).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, the menstrual cycle is yet another important factor to consider. Women show increased fatigue in the middle of the menstrual cycle when estrogen levels peak [ 92 ]. This phase is called the follicular phase, where the levels of sympathetic activity of the central nervous system are higher, coinciding with the highest concentration in estrogen levels during the menstrual cycle.…”
Section: Psychological and Behavioral Modifications And Conditioning ...mentioning
confidence: 99%
“…The animal swimming experiment is one of the important indices to evaluate the antifatigue effect of healthy food ( 30 ). Therefore, we evaluated the swimming ability of mice after gavaging FPNL and PNL ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%